(untitled) (Iranian Journal of Kidney Diseases, 2014)
Familial Mediterranean fever (FMF) is an inherited auto-inflammatory disorder. Secondary AA amyloidosis is the most devastating complication of FMF. Nonamyloid renal involvements have also been reported in association with FMF, including vasculitis, focal and diffuse glomerulonephritis, and IgA nephropathy. We describe a patient with FMF and E148Q mutation who presented with massive proteinuria, elevated serum creatinine level, and acute glomerulonephritis picture. Disease remission was achieved after treatment with corticosteroids and colchicine.